2015
DOI: 10.1097/fbp.0000000000000143
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-like and anxiolytic-like effects of hydrogen sulfide in streptozotocin-induced diabetic rats through inhibition of hippocampal oxidative stress

Abstract: Depression is highly prevalent in individuals with diabetes, and depressive symptoms are less responsive to current antidepressant therapies. Oxidative stress plays a major role both in the pathogenesis of diabetes and in major depression and anxiety disorders. Hydrogen sulfide (H2S), the third gaseous mediator, is a novel signaling molecule in the brain that has both antioxidative activity and antidepressant-like and anxiolytic-like effects. We hypothesized that H2S could produce antidepressant-like and anxio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
37
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 61 publications
(68 reference statements)
9
37
1
Order By: Relevance
“…Further, the diabetes modelling in mice using STZ increased lipid peroxidation, decreased TAC, and disturbed oxidative stress steady state in the mouse brain, similar to previous studies [5,9] in which it was reported that diabetes induction using STZ increased lipid peroxidation and decreased Color version available online TAC in the rodent brain. A probable explanation could be that insulin signaling systems are turned off in a diabetic state, leading to distortion of glucose metabolism and changes in mitochondrial energy production, reduced ATP production, and increased reactive oxygen species in the brain as reported previously [20] .…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Further, the diabetes modelling in mice using STZ increased lipid peroxidation, decreased TAC, and disturbed oxidative stress steady state in the mouse brain, similar to previous studies [5,9] in which it was reported that diabetes induction using STZ increased lipid peroxidation and decreased Color version available online TAC in the rodent brain. A probable explanation could be that insulin signaling systems are turned off in a diabetic state, leading to distortion of glucose metabolism and changes in mitochondrial energy production, reduced ATP production, and increased reactive oxygen species in the brain as reported previously [20] .…”
Section: Discussionsupporting
confidence: 74%
“…The depressive-like behavior has been observed in diabetic animals using different behavioral tasks such as tail suspension and forced swimming tests [8,9] . Also, evidence has shown that inhibition of hippocampal oxidative stress can exert antidepressant-like effects on diabetic animal models [9] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the neurotoxicity of corticosterone plays an important role in the development of depression [14,15]. In addition, our recent studies have shown that H 2 S has antidepressant-like effect [25,26]. Thus, we suggest that the anti-depressive effect of H 2 S may be related to its inhibitory effect against the corticosterone-induced neurotoxicity…”
Section: Discussionmentioning
confidence: 78%
“…A recent report has documented that the endogenous H 2 S level is decreased in chronic unpredictable mild stress (CUMS) [24]. In addition, our recent studies showed that H 2 S could prevent depressive-like actions in the behavioral models of depression [25,26]. These data imply that H 2 S may be a potential therapeutic target for the treatment of depression.…”
Section: Introductionmentioning
confidence: 75%